Comparative Investigation of Hydrogen Embrittlement of Palladium Deposits from Ionic Liquid and Aqueous Electrolyte1. Issue 2 (30th June 2014) - Mehner, Thomas; Nickel, Daniela; Nehrkorn, Sissy; Yulinova, Alexandra; Pügner, Marc; Scharf, Ingolf; Lanzinger, Gloria; Böck, Reinhard; Lampke, Thomas
<x xml:space="preserve">Abstract</x> Palladium layers deposited from aqueous electrolytes are susceptible to hydrogen embrittlement. Such layers are compared with deposits from anhydrous ionic liquid (IL) concerning residual stresses, indentation hardness, and wear. IL layers show a ductile deformation behavior (figure), whereas the conventionally deposited layers are significantly more brittle. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>